PEMURNIAN GALUR JAGUNG MANADO KUNING (Zea mays L.) KERNAL PUTIH DENGAN METODE EAR TO ROW - Injili Rianti Runtunuwu; Semuel D Runtunuwu; Sesilia Wanget (COCOS, 2018)
ABSTRACT The purpose of this study was to determine the purity level of the F2 white kernel Manado yellow line using the Ear To Row Method. This research was cunducted in april until august 2017 in Kalasey 1 village, District of Mandolang, Minahasa Regency, North Sulawesi Province. In this study the observational variables included the percentage of white kernal color and other color percentage of red beard color. In research on cobs one with white clover color characterization, the percentage of white kernels ( 100% in one ear) was 95,85% and the reaming 4,14% were cobs which had a white-yellow mixed kernel color. On the white cactus plant cobs obtained a percentage of 63,2% and the red clover obtained with a percentage of 36,8%. In the second ear with red clover, the percentage of white kernel color (100% in one ear) was 96,01% and the remaining 3,39% were cobs which had a mixture of yellow and white. Crop cobs with white taffy obtained a percentage of 22,09% and cobs of plants with red clover obtained a percentage of 77,91%. The results of the purification of F2 lines yellow Manado corn white kernels using the ear to row method shows that there are still a few corn cobs of corn plants that produce yellow white mixed kernel/ seed. This research suggested that further refining is done for the yield of F2 Manado yellow white kernel corn on cob, producing 100% white kernels to determine the level of purity. Keywords : The Purity Level, Corn, White Kernel, Ear To Row